Inquiry Learning Using Flipped Classroom Approach to Improve Students Self Efficacy in Dynamic Fluid Material - Hasbi, Julia Edwina; Chandra, Didi Teguh; Liliawati, Winny (Journal of Natural Science and Integration, 2022)
This study aims to obtain an overview of increasing students' self-efficacy after applying inquiry learning with the flipped classroom approach on dynamic fluid material. The research method used in this research is the mix method. Data analysis techniques are presented in a quantitative descriptive form. The research subjects were students of class XI in one of the public high schools in Kampar Regency, Riau Province with a sampling technique based on certain considerations (purposive sampling). The sample in this study was one class of XI IPA students, totaling 25 students with an average age of 17 years. The research data was obtained through a self-efficacy questionnaire with 28 statements according to the self-efficacy component. The findings of the maximum, minimum and average values of the level of student self-confidence which then after being matched with the table of self-efficacy criteria shows the average level of student self-confidence from moderate (59.4%) to high (68.88%) with the highest average on the generality component. The results showed that inquiry learning with a flipped classroom approach on dynamic fluid materials could increase students' self-efficacy after learning activities with a major effect (d = 1.92) and received positive responses from students in the excelent category.Keywords: inquiry, flipped classroom, self efficacy